Why Configurations (Configurazioni. Research on contemporary poetry, 2022)
The steering committee of Configurations. Research on Contemporary Poetry explains the guidelines and research directions that characterise the journal.
Keywords: Contemporary Italian Poetry; Poetry of the Late 20th century; Literary System; Functionalism; Publishing Studies